Plastic Coverage of a Lentigo-Maligna Defect in the Cheek, an Alternative Practice Concept (London Journal of Medical and Health Research, 2024)
We have already presented our concept to close more extensive defects after tumor resection of basal cell carcinoma in the head and neck region in scientific journals [1, 2]. Essentially, the procedure consists of suturing a defect wound by approximation with an overlocking hem suture. over a period of about 3 months. The granulating wound is additionally covered by a collagen membrane and protected with a custom-made, stitched-on dressing plate. It seems to us to be logical to do this also for resection defects of other resection defects of other entities.
Keywords: Second brain; Gut brainaxis; COVID-19 andmicrobiome; COVID-19 liver effect; Perception; Nursing Student; Induced Abortion.